Food insecurity and time use in elderly vs. non‐elderly: An exploratory analysis. Issue 1 (27th April 2022) - Berning, Joshua; Cleary, Rebecca; Bonanno, Alessandro
Abstract: In the US, elderly households are more food secure than younger households. A possible explanation is that increased time availability enables elderly households to adopt strategies to improve their food security. Using time use data, we find elderly households spend more time in meal preparation and eating time than younger households. Creating a matched dataset of household time use and food security, we find that meal preparation and eating time have a small contribution to differences in food insecurity between older and younger households. However, these relationships are heterogeneous depending upon marital status and age cohort of the household head.